Memory impairment in multiple sclerosis: correlation with deep grey matter and mesial temporal atrophy. Issue 2 (1st October 2008) - Benedict, R H B; Ramasamy, D; Munschauer, F; Weinstock-Guttman, B; Zivadinov, R
Abstract : Background: MRI research in multiple sclerosis (MS) samples reveals pathology in both the cerebral cortex and deep grey matter (DGM). The classical subcortical dementia hypothesis has been ascribed to MS and is supported by studies highlighting the role of thalamic atrophy in neuropsychological outcomes. However, the importance of mesial temporal lobe (MTL) atrophy in MS is largely untested and poorly understood. New structural imaging techniques permit volumetric measures of multiple regions within the MTL lobe and DGM. Objective: To determine the relative importance of MTL and DGM structures in predicting MS performance on memory tests presented in the auditory/verbal and visual/spatial spheres. Methods: Cross sectional analysis of 50 patients with MS undergoing structural brain MRI and neuropsychological testing. Using Freesurfer software, the volumes of the MTL (hippocampus, amygdala) and DGM (thalamus, caudate) structures were calculated and compared with control values. Neuropsychological testing contributed measures of new learning, delayed recall and recognition memory, in the auditory/verbal and visual/spatial memory modalities. Results: Significant correlations between lower regional volume and poorer test performance were observed across all memory tests. For measures of free recall or new learning, DGM volumes were most strongly predictive of outcomes. In contrast, measures of recognition memory were predicted only by MTL volumetric measures. Conclusion: For the first time, the predictive validity of MTL and DGM atrophy were simultaneously compared with MS using reliable and validated neuropsychological measures. This study found that both compartments play significant but different roles in the amnesia of MS.